CYTOKINES AS MEDIATORS OF THE IMMUNE SYSTEM AND THEIR ROLE IN THE PATHOGENESIS OF COMMUNITY-ACQUIRED PNEUMONIA - Berezniakov, V.I.; Korzh, A.N.; Pavlov, S.B.; Yeroshenko, G.A.; Shevchenko, K.V.; Pyvovar, N.M. (World of Medicine and Biology, 2021)
The clinical and immunological examination of patients with community-acquired pneumonia has been carried out that included the study of the IL-2, IL-4, IL-6, IL-8 and TNFα cytokines’ system. Immune system disorders that determine the severity of pneumonia, the amount of inflammatory damage to the lung tissue, disrupted elimination of the immune complexes have been found. These tendencies to a decrease in the immunoglobulins M and G result in a moderate course of community-acquired pneumonia and lobar lesions of the lungs, and the immune system disorders are reliably associated with imbalance of cytokines, with a predominance of their pro-inflammatory activity and a decrease in regulatory functions. The findings of the immunological monitoring indicate that standard antibiotic therapy in patients with community-acquired pneumonia leads to its clinical and radiological resolution, though it is not accompanied by the normalization of immunity parameters. The imbalance of the cytokine component of immunity justifies the need for further development of pathogenetic, as well as immunocorrective therapy, in patients with community-acquired pneumonia.
Keywords: community-acquired pneumonia; pathogenesis; immunity; cytokines